2017
DOI: 10.21077/ijf.2017.64.special-issue.76210-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different probiotic strains for growth performance and immunomodulation in Pacific white shrimp Penaeus vannamei Boone, 1931

Abstract: The use of antibiotics in aquaculture can prevent certain diseases, however, its use is highly restricted due to several environmental and human health problems like development of antibacterial resistance. Probiotics are widely used for improving production of aquatic animals by means of improving water quality as well as by nutritional and immune modulation in animals thus, helping in preventing diseases. The present study was aimed to evaluate different strains of probiotics viz., a commercial probiotic, Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
2
1
0
Order By: Relevance
“…The total Vibrio count was found at reduced levels in CW + IP, BFT, and BFT + IP. The results of the present study are in agreement with the findings of Aguilera-Rivera et al [39] and Sundaram et al [40], who recorded a reduction in the population of Vibrio in the rearing system. Zhao et al [41] also reported that inoculating Bacillus into BFT water resulted in a decrease in the population of total Vibrio.…”
Section: Discussionsupporting
confidence: 94%
“…The total Vibrio count was found at reduced levels in CW + IP, BFT, and BFT + IP. The results of the present study are in agreement with the findings of Aguilera-Rivera et al [39] and Sundaram et al [40], who recorded a reduction in the population of Vibrio in the rearing system. Zhao et al [41] also reported that inoculating Bacillus into BFT water resulted in a decrease in the population of total Vibrio.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover PER values obtained were also gains support from both Feeding, Absorption and Conversion rates of feeds, which showed a significant increase (p<0.05) in the present study. Similar kind of observations were also reported with Prawns M. rosenbergii, L. vannamei, P. monodon, fish Clarius gariepinus, Oncorhynchus mykiss, Oreochromis niloticus through the incorporation of probiotic bacteria with feeds and Bioflocs incorporation into culture media [50,[66][67][68] . Biofloc addition in the form of selected external Carbon sources facilitates the growth of Heterotrophic bacteria in the Culture Operation, which subsequently provides the supplementary feeding materials, thereby significantly increases the protein content in the Candidate Species of culture.…”
Section: Growth Performance Studiessupporting
confidence: 78%
“…Furthermore, the feeding, absorption, and conversion rates of feeds all demonstrated a substantial increase (p<0.05) in the current investigation, supporting the PER values that were obtained. By incorporating probiotic bacteria with feeds and Bioflocs into culture medium, similar kinds of observations were also observed with prawns M. rosenbergii, L. vannamei, P. monodon, fish Clarius [49][50][51]. The addition of biofloc, in the form of specific external carbon sources, promotes the growth of heterotrophic bacteria in the culture operation, which in turn supplies additional feeding materials and raises the protein content of the Candidate Species of culture to a large degree.…”
Section: Growth and Feed Performance Studiesmentioning
confidence: 62%